Transcatheter Interatrial Shunts for the Treatment of Heart Failure with Preserved Ejection Fraction - Bhardwaj,Anju (2021)
Abstract Heart failure with preserved ejection fraction (HFpEF) is a clinical syndrome, which accounts for about 50% of patients with heart failure (HF). The morbidity and mortality associated with HFpEF is similar to HFrEF. Clinical trials to date have failed to show a benefit of medical therapy for HFpEF, which may due to lack of uniform phenotypes and heterogeneous population. In addition, medical therapy proven for HFrEF may not address the pathophysiologic basis for HFpEF. Left atrial remodeling and dysfunction is central to HFpEF and accounts for secondary pulmonary hypertension and pulmonary vascular congestion that frequently occurs with exertion. Interatrial shunts represent a novel treatment modality for HFpEF. These shunts allow for left atrial decongestion and a reduction in pulmonary venous hypertension during exercise leading to improvements in hemodynamics, functional status and quality of life. Trials to date have demonstrated safety and short-term efficacy of these devices for HFpEF. The long-term benefits are currently being evaluated in ongoing trials. If effective, the use of interatrial shunts may be a new therapeutic paradigm for the treatment of HFpEF.